Design and implementation of sigma delta modulators (ΣΔM) for class D audio amplifiers using differential pairs - Pereira, Nuno; Paulino, Nuno (Springer International Publishing, 2015)
This book focuses on the design of a 3rd Order CT-ΣΔM where the integrator stages of the filter are implemented with Bipolar-Junction Transistors (BJT) differential pairs. These circuits are fully analyzed and the design method is carefully explained. The design method is validated through experimental measurements of several prototype circuits.